Instituição Pia nossa Senhora das Graças: assistência e educação de crianças pobres, órfãs e abandonadas em Belém (1943-1975) - CALLOU, Maria Lucirene (Universidade Federal do Pará, 2017)
This research aims to identify and analyze the relevance assistance, philanthropic and educational of the Instituição Pia Nossa Senhora das Graças in attendance poor children, orphans and abandoned in Belém. For this is intended to: 1). Identify and analyze the purpose political, educational and the religious IPNSG; 2) Highlight the educational practices and assistance for the attendance poor childhood; 3) Relate the partnership actions that the institution held to remain active in the assistance and education of children’s.; 4) Characterize the profile of children seen in IPNSG; The study is located in the field of history of the educational institution, it will be reviewed by the bias of Cultural History of Roger Chartier, who sees social relations through practices and representations. The research is documentary, was used as historical sources clippings newspapers, minutes of the institution, balance sheets, statutes, reports, children admission sheets, photos and testament of Ilda Martins, who treated on the institution. After mapping the content of the matters discussed in the documents, the following categories of analysis for this study were elected: Institution, Childhood, Assistance, Education and boarding school. The origin of IPNSG happens with the creation of Antoniana Youth Association (1943-1949), linked to the Order of Friars Minor Capuchins and becomes institution in 1950. The institution promoted many religious campaigns and attempted to raise funds for the construction of the poor child's home in Belém. It was found that from as 1959 start attendance of children in boarding school and finished the construction of the building in 1961. Initially the institution assisted boys and girls of different ages, gave primary education, Christian religious teachings, shelter materials and household education only for girls. We found that the institution remained active partnerships with Department of Education, LBA, FBESP, FUNABEM, FUNPAPA, politicians and businessmen. From 1967 onwards, the service in boarding is meant only to girls and day school for both sexes, was offered primary education, household education, spiritual support and material. The institution came at a critical time in Belem, where public health was precarious and poverty was recurrent social condition among resident families in the city Belém. Like this, the boarding school for many families was the solution to that poor children receive protection and education The Instituição Pia Nossa Senhora das Graças based on Christian doctrine, worked for educate and protect children of the abandonment, orphanhood and poverty.